Metformin targets multiple signaling pathways in cancer - Yong Lei; Yanhua Yi; Yang Liu; Xia Liu; Evan T. Keller; Chao-Nan Qian; Jian Zhang; Yi Lu (Chinese Journal of Cancer, 2017)
Abstract Metformin, an inexpensive and well-tolerated oral agent commonly used in the first-line treatment of type 2 diabetes, has become the focus of intense research as a candidate anticancer agent. Here, we discuss the potential of metformin in cancer therapeutics, particularly its functions in multiple signaling pathways, including AMP-activated protein kinase, mammalian target of rapamycin, insulin-like growth factor, c-Jun N-terminal kinase/mitogen-activated protein kinase (p38 MAPK), human epidermal growth factor receptor-2, and nuclear factor kappaB pathways. In addition, cutting-edge targeting of cancer stem cells by metformin is summarized.